High‐Resolution Imaging of Interaction Between Thrombus and Stent‐Retriever in Patients With Acute Ischemic Stroke. Issue 13 (3rd July 2018) - Autar, Anouchska S. A.; Hund, Hajo M.; Ramlal, Sharad A.; Hansen, Daniël; Lycklama à Nijeholt, Geert J.; Emmer, Bart J.; de Maat, Moniek P. M.; Dippel, Diederik W. J.; van der Lugt, Aad; van Es, Adriaan C. G. M.; van Beusekom, Heleen M. M.; ,
Abstract : Background: Currently, acute ischemic stroke is still a leading cause of mortality and morbidity. Approximately 2 years ago, mechanical thrombectomy was proven beneficial as a revolutionary new therapy for stroke in the MR‐CLEAN trial (A Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands). However, the mechanisms by which the thrombectomy device, or stent‐retriever, interacts with the thrombus are largely unknown. A better understanding could lead to improved efficacy of mechanical thrombectomy devices. Methods and Results: Seven stent‐retrievers with thrombi still entrapped were collected directly after thrombectomy. The stent‐retrievers were studied using micro computed tomography, followed by scanning electron microscopy and light microscopy. Two independent observers rated interaction type and thrombus surface structure (porous filamentous or dense) at the interaction sites. A total of 79 interaction sites between thrombus and stent‐retriever were categorized. Thrombus‐stent‐retriever interaction was found to be adhesive (n=44; 56%) or mechanical (n=35; 44%). Adhesive interaction was most frequently observed at interaction sites with a dense surface, compared with interaction sites with a porous filamentous fibrin surface (38/58; 66% versus 6/21; 29%, P =0.011). Conclusions: The interaction between thrombus and stent‐retriever was predominantly adhesive, not mechanical. Adhesive interaction was strongly associated with the presence of a dense thrombus surface without a porous filamentous fibrin network.